Engineering separations unit operations for nuclear processing - Peterson, Reid A. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Engineering Separations Unit Operations for Nuclear Processing provides insight into the fundamentals of separations in nuclear materials processing not covered in typical texts. This book integrates fuel cycle and waste processing into a single, coherent approach, demonstrating that the principles from one field can and should be applied to the other. It provides historical perspectives on nuclear materials processing, current assessment and challenges, and how past challenges were overcome. It also provides understanding of the engineering principles associated with handling nuclear materials. This book is aimed at researchers, graduate students, and professionals in the fields of chemical engineering, mechanical engineering, nuclear engineering, and materials engineering.
Chapter 1 Overview of Process Flowsheets 1 Reid A. Peterson Chapter 2 Uranium Fuel Dissolution 11 Calvin H. Delegard Chapter 3 Precipitation and Crystallization Processes in Reprocessing, Plutonium Separation, Purification, and Finishing, Chemical Recovery, and Waste Treatment 51 Calvin H. Delegard and Reid A. Peterson Chapter 4 Solvent Extraction in the Nuclear Fuel Cycle 145 Gabriel B. Hall, Susan E. Asmussen, and Amanda J. Casella Chapter 5 Filtration 189 Philip P. Schonewill Chapter 6 Ion Exchange 251 Reid A. Peterson, Garrett Brown, and Amy M. Rovira Chapter 7 Non-aqueous Processing 305 Michael F. Simpson and Andrew M. Casella
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Energy; TECHNOLOGY / Engineering / Chemical & Biochemical; Nuclear reactors -- Materials; Nuclear fuel elements; Radioactive wastes